Pengaruh Pendapatan, Persepsi Risiko Dan Bias Overconvidence Terhadap Keputusan Berinvestasi Pada Pasar Modal Syariah: Studi Pada Idx Cabang Kota Bengkulu - Agustina, Erti; Mursalin, Supardi; Hariyadi, Rizky (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
The purpose of this study is to find out and analyze the influence of income, risk perception, and overconfidence bias on the investment decisions of investors listed on the Indonesia Stock Exchange (IDX) in Bengkulu City. Investment decisions are an important aspect of the financial world, where various factors can influence a person in making decisions to invest. To test the influence of these three variables, this study uses a quantitative method with primary data collection techniques conducted through the distribution of questionnaires to 97 respondents who are IDX investors in Bengkulu City. The data obtained was then analyzed using multiple regression techniques with the help of the SPSS. Based on the results of the research and discussion, it was found that income did not have a significant influence on investment decisions, with a significance value of 0.063 which was greater than 0.05. Meanwhile, risk perception has a significant influence on investment decisions, with a significance value of 0.000 which is less than 0.05. In addition, the overconfidence bias also had a significant effect on investment decisions with a significance value of 0.007 which was smaller than 0.05. Thus, it can be concluded that risk perception and overconfidence bias have a significant impact on investors' investment decisions in the Islamic capital market, while income does not have a significant influence.